2003
DOI: 10.1242/dev.00349
|View full text |Cite
|
Sign up to set email alerts
|

The zinc-finger protein CNBP is required for forebrain formation in the mouse

Abstract: Mouse mutants have allowed us to gain significant insight into axis development. However, much remains to be learned about the cellular and molecular basis of early forebrain patterning. We describe a lethal mutation mouse strain generated using promoter-trap mutagenesis. The mutants exhibit severe forebrain truncation in homozygous mouse embryos and various craniofacial defects in heterozygotes. We show that the defects are caused by disruption of the gene encoding cellular nucleic acid binding protein (CNBP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
71
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 57 publications
3
71
0
Order By: Relevance
“…Knockout experiments in mice have shown that CNBP is essential for forebrain formation (43). In conjunction with other studies, which have demonstrated an increase of c-myc promotor activity and cell proliferation upon overexpression of CNBP (44), it has been proposed that CNBP regulates forebrain formation through induction of c-Myc expression, which in turn stimulates cell proliferation and differentiation (43).…”
Section: Fliesmentioning
confidence: 97%
“…Knockout experiments in mice have shown that CNBP is essential for forebrain formation (43). In conjunction with other studies, which have demonstrated an increase of c-myc promotor activity and cell proliferation upon overexpression of CNBP (44), it has been proposed that CNBP regulates forebrain formation through induction of c-Myc expression, which in turn stimulates cell proliferation and differentiation (43).…”
Section: Fliesmentioning
confidence: 97%
“…CNBP is highly conserved among human, mouse, rat, chicken, Xenopus species and fish [8]. The disruption of CNBP caused severe forebrain truncation and defective neural crest development [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…During embryogenesis, the CNBP expression patterns have been analyzed in Bufo arenarum, Xenopus leavis, Danio rerio, mouse and chick [3,8,9,[11][12][13]. During early embryogenesis, CNBP mRNA could be detected in the The nucleotide sequence data reported in this paper have been submitted to the GenBank under accession number: CagCNBP (AY773183).…”
Section: Introductionmentioning
confidence: 99%
“…During early embryogenesis, CNBP mRNA could be detected in the The nucleotide sequence data reported in this paper have been submitted to the GenBank under accession number: CagCNBP (AY773183). unfertilized eggs and in the all embryonic cells in frog, zebrafish, cattle, chick and mouse [3,8,9,[11][12][13]. In mouse, during organogenesis, CNBP expresses predominantly in forebrain and midbrain, and plays important roles in cell proliferation and tissue patterning [12], and it is essential for the forebrain induction and specification [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation